Efficacy and safety of FOLFIRI/aflibercept in second‐line treatment of metastatic colorectal cancer in a real‐world population: Prognostic and predictive markers - Ana Fernández Montes; Nieves Martínez Lago; Marta Covela Rúa; Juan de la Cámara Gómez; Paula González Villaroel; José Carlos Méndez Méndez; Mónica Jorge Fernández; Mercedes Salgado Fernández; Margarita Reboredo López; Guillermo Quintero Aldana; María Luz Pellón Augusto; Begoña Graña Suárez; et al. (Cancer Medicine)
Abstract Purpose The phase III VELOUR trial demonstrated efficacy with combined FOLFIRI‐aflibercept in patients with metastatic colorectal cancer previously treated with oxaliplatin with or without bevacizumab versus placebo. The effect of FOLFIRI‐aflibercept in routine clinical practice was evaluated. Methods/Patients Overall survival (OS), progression‐free survival (PFS), response and safety were analysed for 78 patients treated with FOLFIRI‐aflibercept at six GITuD institutions. Exploratory analyses of prognostic and predictive markers of efficacy were performed. Results Patients had good general status (PS 0‐1 96.2%), tumours were mostly RAS‐mutant (75.6%), synchronous (71.8%), and left‐sided (71.8%). Prior therapy included bevacizumab (47.4%) and anti‐EGFR agents (12.8%). PFS was longer for metachronous than synchronous tumours (11.0 vs 5.0 months, P = 0.028), and for left‐colon tumours (7.0 vs 3.0 months, P = 0.044). RAS‐mutant status, first‐line treatment and primary tumour surgery did not impact PFS. The disease control rate was 70.5%. The most common grade 3/4 toxicities were neutropenia (15.3%), asthenia (10.3%), diarrhea and mucositis (6.4% each). Dysphonia was reported in 39.7% of patients, and grade 3 hypertension in 3.8%. Development of hypertension (any grade) was significantly associated with a reduced risk of progression by multivariate analysis (HR = 2.7; 95%CI 1.3‐5.4; P = 0.001). Conclusions Efficacy with FOLFIRI‐aflibercept in a real‐life population was in line with results from the pivotal trial and toxicity was manageable with treatment adaptation. Survival outcomes were not impacted by primary tumour location, RAS‐mutant status, first‐line treatment or primary tumour surgery. Hypertension may be a surrogate marker of efficacy in this patient population.